A whole cell-based Matrix-assisted laser desorption/ionization mass spectrometry lipidomic assay for the discovery of compounds that target lipid a modifications - Tang, Wenhao; Osborne, Joanne; Dortet, Laurent; Larrouy-Maumus, Gerald (Frontiers in Microbiology, 2023)
Matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS) is a powerful analytical technique that has been applied to a wide variety of applications ranging from proteomics to clinical diagnostics. One such application is its use as a tool for discovery assays, such as monitoring the inhibition of purified proteins. With the global threat from antimicrobial-resistant (AMR) bacteria, new and innovative solutions are required to identify new molecules that could revert bacterial resistance and/or target virulence factors. Here, we used a whole cell-based MALDI-TOF lipidomic assay using a routine MALDI Biotyper Sirius system operating in linear negative ion mode combined with the MBT Lipid Xtract kit to discover molecules targeting bacteria that are resistant to polymyxins, which are considered last-resort antibiotics. A library of 1200 natural compounds was tested against an E. coli strain expressing mcr-1, which is known to modify lipid A by adding phosphoethanolamine (pETN), making the strain resistant to colistin. Using this approach, we identified 8 compounds that led to a decrease in this lipid A modification by MCR-1 and could potentially be employed to revert resistance. Taken together, as-proof-of-principle, the data we report here represent a new workflow based on the analysis of bacterial lipid A by routine MALDI-TOF for the discovery of inhibitors that could target bacterial viability and/or virulence.